Assessment of Anxiolytic and Anti-depressant Activities of different Extracts of Catharanthusroseus Leaves in Experimental Animals - Shinde, Manisha; Chaudhari , Sanjay; Ritu, Gilhotra (International Journal of Psychosocial Rehabilitation, 2020)
Catharanthus roseus leaves are investigated to assess anxiolytic and antidepressant activity in experimental animal models. Successively extracted petroleum ether, chloroform, and ethanolic extracts were used in the experiment. Anxiolytic and antidepressant activity was studied using the elevated plus maze and forced swim test, respectively. Oral administration of 200 and 400 mg/kg petroleum ether extract shows significant (p